Enhancing Students’ Understanding of Fiqh through the Jigsaw Model at MA NW Bebuak - Susmi Laila Hidayah; Elmiati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students’ understanding of Fiqh at MA NW Bebuak through the implementation of the Jigsaw model. Fiqh, as a central component of Islamic studies, requires students to comprehend complex concepts and apply them in daily life. Traditional methods of teaching Fiqh often result in passive learning and limited student engagement. The Jigsaw model, a cooperative learning technique, divides students into small groups, where each group is assigned a portion of the topic to study, and then share their findings with the rest of the class. This research explores how the Jigsaw model can foster active participation, improve comprehension, and enhance collaborative learning among students. The study was conducted in two cycles, involving 10th-grade students at MA NW Bebuak. In each cycle, students were divided into groups, each responsible for learning different sections of a Fiqh topic, such as the rules of fasting, zakat, or prayer. After studying their assigned sections, students shared their knowledge with other groups, thus allowing them to gain a comprehensive understanding of the topic. Data were collected through observations, student surveys, and pre- and post-tests to measure improvements in student understanding and engagement. The findings indicate that the Jigsaw model significantly improved students’ understanding of Fiqh. Students demonstrated greater engagement and enthusiasm during the lessons, actively participating in discussions and teaching their peers. Moreover, students reported feeling more confident in their ability to apply Fiqh principles in real-life scenarios. This research suggests that the Jigsaw model is an effective strategy for improving students’ comprehension of Fiqh and promoting a more interactive and collaborative learning environment.